Brexit and workers' rights. (1st January 2021) - Countouris, Nicola; Ewing, Keith
Abstract : The labour law of the UK and of other Member States is, and will become, more truly European than appears from the formal imprint of EC labour law. It is European rather by reflecting the cumulative experience of national labour laws, filtered through the prism of the EC institutions and refined in the crucible of the developing European polity. The tendency towards convergence of UK labour law with the labour laws of other Member States of the EC is driven in the main by the institutional pressures of EC membership, and, to a lesser extent, is the consequence of the workings of the international economy and, though less significant, a single European labour market. The dynamic of this convergence process is complex and its results are far from complete.